A narrative literature review to inform the development of a health threats preparedness framework in Ireland - Marron, Louise; Gilroy, James; Williams, Michelle; Parlour, Randal; Boland, Máirín (Frontiers in Public Health, 2025)
IntroductionPublic health emergency preparedness requires capacities and capabilities to respond to a diverse range of health threats. A key objective of Ireland’s recent Health Protection Strategy is to enable preparedness, prevention, early detection and optimal response to health threats from all-hazards. We aimed to identify priority areas for inclusion in an evidence-based health threats preparedness framework, using lessons from the COVID-19 pandemic, to inform a national health threats strategy and a strengthened emerging health threats function for Ireland.MethodsWe conducted a narrative literature review to inform the health threats preparedness framework development. We carried out literature searches in two phases, from 2017 to 2022, followed by an updated search covering 2022–2024, to ensure all relevant, recent literature was captured. We used a data extraction tool to collate priority areas reported.ResultsOverarching priorities for health threats preparedness are rapid decision-making, an outcomes-based, and ethical approach. Health threats preparedness should include a risk-based, all-hazards, One Health approach, aligned with legislation. Multisectoral partnerships, collaboration and communication nationally and internationally are key, alongside clear governance structures and monitoring and evaluation. Adequate resources are required to operationalize effective and sustainable preparedness. Public health leadership must be to the fore.ConclusionAn effective health threats preparedness approach is legislatively mandated for European Member States. This evidence review highlights priority areas for a comprehensive health threats preparedness framework. This framework supports the development of a strengthened emerging health threats function in Ireland and may inform other Member States’ preparedness.